Monitoring of the Ecological Condition of Regional Economic Systems in the Context of Sustainable Development - TULCHYNSKA, Svitlana; POPELO, Olha; MARHASOVA, Viktoriia; NUSINOVA, Olena; ZHYGALKEVYCH, Zhanna (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021DO - 10.14505//jemt.v12.5(53).06, 2021)
The article is devoted to monitoring the ecological condition of regional economic systems in the context of sustainable development on the example of the regions of Ukraine. Monitoring the ecological condition of regional economic systems makes it possible to monitor qualitative changes in the environment components and their compliance with the established requirements in terms of sustainable development in the direction of environmental safety, maximum efficient use of nature, preservation of the environment for future generations. The tasks of monitoring the ecological condition of regional economic systems in the context of sustainable development are  singled out, which include: implementation of the systematic diagnostics of the ecological condition of regions; timely and complete informing of regional and local authorities on the real status of the environmental component of sustainable development; analytical decision-making to ensure environmental safety of regions; development of projects on environmental protection, as well as careful and rational use of regional resources. The main objective conditions, which should include monitoring of the ecological condition of regional economic systems in the context of sustainable development, are defined.  A methodological approach for monitoring is proposed, which provides for: determination of indicators for the ecological status assessment; normalization of indicators and isolation of stimulants and destimulants from them; calculation of the integrated index of the ecological state of regional economic systems; grouping of regions by values of the integrated index of the ecological condition. Monitoring was carried out in accordance with the proposed methodological approach to the ecological condition of the regions of Ukraine and suggested directions for improving the ecological condition of regional economic systems.